2020
DOI: 10.1371/journal.pntd.0008896
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic differentiation of Zika and dengue virus exposure by analyzing T cell receptor sequences from peripheral blood of infected HLA-A2 transgenic mice

Abstract: Zika virus (ZIKV) is a significant global health threat due to its potential for rapid emergence and association with severe congenital malformations during infection in pregnancy. Despite the urgent need, accurate diagnosis of ZIKV infection is still a major hurdle that must be overcome. Contributing to the inaccuracy of most serologically-based diagnostic assays for ZIKV, is the substantial geographic and antigenic overlap with other flaviviruses, including the four serotypes of dengue virus (DENV). Within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 48 publications
0
2
1
Order By: Relevance
“…Of note, since underlying active coinfections (like human immunodeficiency virus, hepatitis C virus, and hepatitis B virus) were excluded from the study, we cannot exclude their potential impact on our classifier. While the CDR3β region has been explored most in TCR-based exposure classifiers [ 6 , 7 , 9 , 33 , 34 ], we observed that the combination of both the CDR3α and CDR3β regions of the TCR tended towards greater diagnostic performance than either of the regions separately (however, no statistical significance was reached).…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Of note, since underlying active coinfections (like human immunodeficiency virus, hepatitis C virus, and hepatitis B virus) were excluded from the study, we cannot exclude their potential impact on our classifier. While the CDR3β region has been explored most in TCR-based exposure classifiers [ 6 , 7 , 9 , 33 , 34 ], we observed that the combination of both the CDR3α and CDR3β regions of the TCR tended towards greater diagnostic performance than either of the regions separately (however, no statistical significance was reached).…”
Section: Discussioncontrasting
confidence: 54%
“…Recently developed TCR repertoire profiling technology (through TCR sequencing) allows identification of infectious disease–associated T-cell imprints. For instance, an exposure classifier based on the TCR repertoire distinguished naive from smallpox-vaccinated mice [ 8 ], Zika virus–exposed from dengue virus–exposed mice [ 7 ], and CMV-seropositive from CMV-seronegative human individuals [ 5 , 6 ]. Recently, the first test based on this technology received US Food and Drug Administration approval for the detection of SARS-CoV-2 exposure (T-Detect, Adaptive Biotechnologies [ 9 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation